Pengaruh Dana Transfer terhadap Kemandirian Keuangan Daerah pada Kabupaten/Kota di Provinsi DIY 2014–2024 - Ayu Kinanti, Marsdika; Santorry, Santorry (JURNAL MANAJEMEN KEUANGAN PUBLIK, 2025)
This study aims to analyze the effect of Intergovernmental Fiscal Transfers—consisting of the General Allocation Fund (DAU), Special Allocation Fund (DAK), and Revenue Sharing Fund (DBH)—as well as the Special Autonomy Fund on Regional Financial Independence (KKD) in the regencies/municipalities of the Special Region of Yogyakarta (DIY). The study also employs Gross Regional Domestic Product (GRDP) as a control variable. The sample comprises five regencies/municipalities observed over an 11-year period, from 2014 to 2024. The analytical method applied is panel data regression with a fixed effect approach. The results show that three independent variables have a negative effect on KKD, namely DAU (negative and significant), DAK (negative and insignificant), and the Special Autonomy Fund (negative and insignificant). Conversely, DBH exerts a positive and significant effect on KKD. These findings indicate that not all forms of transfers from the central government are capable of enhancing regional financial independence.